Early discontinuation of dual antiplatelet therapy via acetylsalicylic acid cessation in patients with acute coronary syndrome undergoing percutaneous coronary interventions to reduce the bleeding risk - O. V. Averkov (Российский кардиологический журнал)
Early percutaneous coronary intervention (PCI) and long-term aggressive antithrombotic treatment based on dual antiplatelet therapy (DAPT) are the most important elements in the treatment of patients with acute coronary syndrome (ACS). The most studied and recommended for ACS is the 12-month DAPT (combination of acetylsalicylic acid (ASA) and P2Y12 receptor antagonist). Bleeding events due to DAPT after ACS and after PCI forced the search for approaches aimed at reducing the risk of such complications, especially noticeable when using a powerful blocker of the P2Y12 receptor of platelets. One of the recently identified solutions turned out to be early (1-3 months after the therapy initiation) discontinuation of ASA with continued administration of one antiplatelet agent (P2Y12 receptor antagonist). The article provides arguments in favor of this approach.